Solubility modelling, solvent effect and preferential solvation of allopurinol in aqueous co-solvent mixtures of ethanol, isopropanol, N, N-dimethylformamide and 1-methyl-2-pyrrolidone. (April 2019) - Li, Xinbao; Liu, Yinping; Zheng, Min; Zhang, Nan; Farajtabar, Ali; Zhao, Hongkun
Graphical abstract: Highlights: Allopurinol solubility in four aqueous co-solvent mixtures was determined and correlated. Solvent effect was studied based on linear solvation energy relationships approach. Preferential solvation of allopurinol in aqueous co-solvent mixtures were derived. Abstract: The equilibrium solubility data of allopurinol in aqueous co-solvent mixtures of ethanol, isopropanol, N, N -dimethylformamide (DMF) and 1-methyl-2-pyrrolidone (NMP) was experimentally determined by a saturation shake-flask method within the temperatures from 293.15 K to 333.15 K under atmospheric pressure. It was found that in the (DMF + water) and (NMP + water) systems, the solubilities of allopurinol increased with increasing temperature and DMF (NMP) composition. However in the (ethanol + water) and (isopropanol + water) systems, they increased at first and then decreased with an increase in mass fractions of ethanol and isopropanol. The determined solubility values were correlated by using the Jouyban-Acree, van't Hoff-Jouyban-Acree and Apelblat-Jouyban-Acree models obtaining average relative deviations lower than 6.84% for correlative studies. Preferential solvation parameters of allopurinol were derived by means of the inverse Kirkwood-Buff integrals method. There were significant different behaviours of the allopurinol between in ethanol (isopropanol) + water and DMF (NMP) + water mixtures. The preferential solvation parameter δx 1, 3 by co-solvent is positive in the regions of 0.25 < x 1 < 0.56–0.57 for ethanol, 0.20 < x 1 < 0.52–0.53 for isopropanol, 0.20 < x 1 < 1 for DMF and 0.16 < x 1 < 1.00 for NMP. It is conjecturable that in these regions, where allopurinol is preferentially solvated by the co-solvents, allopurinol is acting as a Lewis acid with ethanol (isopropanol, DMF or NMP) molecules. Furthermore, the main effects of solvent on the solubility were analysed by linear solvation energy relationships approach taking Kamlet-Taft scales as empirical solvent parameters.